Trend of centenarian deaths in Hong Kong between 2001 and 2010. Issue 6 (5th July 2016) - Yu, Ruby; Tam, Wilson; Woo, Jean
Abstract : Aim: To examine the trends in the leading causes of deaths in centenarians in Hong Kong. Methods: Descriptive analyses of vital statistics data on mortality in Hong Kong from 2001 to 2010 were carried out. Results: The number of centenarians' deaths increased by 136% in 10 years, from less than 28 men and 166 women in 2001 to 80 men and 378 women in 2010. During the study period, the top leading cause of death was pneumonia, accounting for 33.8% of all deaths. In contrast, the other leading causes accounted for much smaller percentages; for example, the second and third leading causes were chronic ischemic heart disease and unspecified dementia, and account for 4.3% and 4.2% of the total, respectively. This cause‐of‐death pattern has remained fairly stable between 2001 and 2010. A total of 985 (30.8%) deaths occurred in January to March. The correlation between the average monthly temperature and the number of deaths was –0.720 ( P  < 0.01). Conclusions: The number of deaths continues to increase in Hong Kong. These trends have major implications for healthcare in an aging population.Geriatr Gerontol Int 2017; 17: 931–936.